Effect of Caffeine on Plasma Glucose and Insulin Response to Mixed Meal Tolerance Test in Type II Diabetes (Medicine Today, 2012)
Caffeine containing beverages is widely used and popular world-wide. Studies showed that caffeine acutely decreased insulin sensitivity in young, non-diabetic adults.3-5 This double-blind study was carried out with habitual coffee drinkers who had at least a 6-months history of type II diabetes. The effects of caffeine on fasting glucose & insulin levels and on glucose & insulin response to a mixed-meal tolerance test were studied. The total daily caffeine intake was 375 mg in a divided schedule. Overnight fast and caffeine abstinence baseline fasting blood samples were drawn then after administration of caffeine (250 mg/day) or placebo they consumed a commercial meal that contained 75 gram of carbohydrate for mixed-meal tolerance test. Comparisons of the AUC2h values demonstrated significant caffeine effects for both plasma glucose and plasma insulin (P < 0.05) responses to the mixed-meal tolerance test. Caffeine did not affect the fasting levels of plasma glucose or insulin when compared with placebo. It may be concluded that acute administration of caffeine plus carbohydrate impaired post-prandial glucose metabolism and insulin responses. Such effects could have implication for the management of type II diabetic patients. Medicine Today 2010 Volume 22 Number 02 Page 73-74 DOI: http://dx.doi.org/10.3329/medtoday.v22i2.12437